MULTIMODAL DISCOURSE ANALYSIS OF EDITORIAL CARTOONS ON INSECURITY IN NIGERIA’S 2023 GENERAL ELECTIONS - Chukwuokoro, Ifeyinwa; Ononye, Chuka; Ngene, Ekwe (EBSU Journal of Social Sciences and Humanities, 2024)
Study analyses editorial cartoons on insecurity in Nigeria’s 2023 general elections. Applying qualitative data analysis, the study examines the semiotic elements that serve as represented participants (RPs) in the cartoons, how such discourse participants are represented in their relations and the multimodal discourse elements utilized to construct meaning in the cartoons. Using Kress and van Leeuwen’s (2006) grammar of visual design model, the study discovered bandits, assassins, terrorists, 1999 Constitution, President Buhari, Independent Oil Marketers, Mr Godwin Emefiele, Lady Justice, and party presidential candidates as the Represented Participants. Some RPs in their relations were represented as initiators of activities that aggravated insecurity while some semiotic elements were discovered to have caused tension which is an index of insecurity. Finally, colour, positioning, font size (for salience), information value, and image size were discovered as multimodal elements whose communicative affordances enhanced meaning construction in insecurity contexts of 2023 general elections in Nigeria.